2015
DOI: 10.1109/tbme.2014.2344854
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Finger and Thumb Muscles Command a Virtual Hand to Allow Individual Finger and Grasp Control

Abstract: Fine-wire intramuscular electrodes were used to obtain EMG signals from six extrinsic hand muscles associated with the thumb, index, and middle fingers. Subjects’ EMG activity was used to control a virtual three-DOF hand as they conformed the hand to a sequence of hand postures testing two controllers: direct EMG control and pattern recognition control. Subjects tested two conditions using each controller: starting the hand from a pre-defined neutral posture before each new posture and starting the hand from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…In general, subjects’ peak use of simultaneous control occurred in the middle of the trial, with greater use of 1-DOF movements at the end. This is similar to previous reports suggesting that subjects tend to use simultaneous control more for gross movements and sequential control for fine positioning [8, 31, 32]. Subjects using linear regression control used fewer 1-DOF movements at the end of the trials than subjects using parallel dual-site control.…”
Section: Discussionsupporting
confidence: 90%
“…In general, subjects’ peak use of simultaneous control occurred in the middle of the trial, with greater use of 1-DOF movements at the end. This is similar to previous reports suggesting that subjects tend to use simultaneous control more for gross movements and sequential control for fine positioning [8, 31, 32]. Subjects using linear regression control used fewer 1-DOF movements at the end of the trials than subjects using parallel dual-site control.…”
Section: Discussionsupporting
confidence: 90%
“…This work constitutes a necessary step toward the evaluation of simultaneous control algorithms in amputees and eventual clinical implementation. The parallel dual-site control approach has been frequently proposed for use with implantable myoelectric recording devices (Weir et al, 2009, Merrill et al, 2011, Birdwell, 2012, Tucker and Peteleski, 1977, Stein et al, 1980), many of which are now in development (Weir et al, 2009, Young, 2009, Bercich et al, 2012, McDonnall et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Williams and Kirsch implemented a system similar to parallel dual-site control using head/neck muscles in patients with tetraplegia (Williams and Kirsch, 2008), but found that subjects chose not to control DOFs simultaneously in a 2-DOF Fitts' Law task. Birdwell found that subjects using parallel dual-site control with EMG from extrinsic finger muscles activated two of three DOFs simultaneously in a virtual task (Birdwell, 2012). However, subjects in the current study controlled all three DOFs at the same time (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure limits the decoding quality of the neural interface because the global EMG is a spatio-temporal summation of action potentials that creates correlations amongst multiple channels and therefore determines an ill posed inverse problem for decoding 20 . Similarly, control methods based on more selective intramuscular EMG recordings have been so far based on global EMG analysis without decoding the contributions of individual motor neurons 21,22 or on a very small number of decoded motor neurons (e.g., two experimentally decoded motor neurons from intramuscular EMG signals in 23 ). Decoupling the neural information contained in the EMG signals, which exactly correspond to the timings of discharge of the efferent nerve fibers, from the shapes of the muscle fiber action potentials would determine a direct interface with the spinal motor neurons.…”
mentioning
confidence: 99%